Alterations of Hemoglobin Fractionation in a Sickle Cell Disease Patient on Voxelotor Therapy. (28th October 2020) - Karimi, S S; Ni, H; Hsu, L L
Abstract: Introduction/Objective: Voxelotor is a molecule that allosterically binds to the alpha-chain of hemoglobin, resulting in increased oxygen affinity. This allosteric inhibition leads to prevention of hemoglobin polymerization and sickling of red blood cells in response to low oxygen tension. Voxelotor has been used to treat patients with Sickle Cell Disease (SCD) and recent literature indicates it may contribute to complex hemoglobin fractionation (HF) elution patterns. We report a novel case of a SCD patient on concurrent Hydroxyurea, Voxelotor and chronic RBC exchange transfusion treatment and discuss the implications of these three treatment modalities on HF and monitoring of SCD. Methods: A 17-year-old female with SCD complicated by frequent vaso-occlusive crisis, and avascular necrosis managed with chronic RBC exchange and Hydroxyurea. Her HF prior to initiation of Voxelotor treatment showed 3.2% HbA2, 51% HbA, 6.0% HbF, and 41% HbS. Voxelotor therapy was initiated at 1500mg/day and HF was performed 10 days later. Whole blood was collected and subjected to High Performance Liquid Chromatography (HPLC) with reflex to RBC solubility and Capillary Electrophoresis. Results: HF performed post-Voxelotor therapy revealed positive sickle solubility with a complex pattern of 2.7% HbA2, 49.2% HbA, 5.3% HbF, 15.7% HbS, 0% HbC, and two additional peaks of a 6.3% peak in the window-D region (retention time of 4.34) and 20.8% of an atypical Hb peak pattern (at the retentuin time of 4.18). The results reflected a complex HF of a HbSS patient on concurrent chronic RBC exchange transfusion, hydroxyurea therapy, and Voxelotor treatment. Post Voxelotor-therapy HF revealed a reduction in HbS from 41% to 15.7% with the emergence of two additional peaks. Chronic RBC exchange transfusion and Hydroxyurea treatment account for the observed fractionation of HbA and HbF, respectively. Based on recent literature, we attribute the emergence of the two additional peaks to Voxelotor therapy. All three therapies led to reduction in HbS. Conclusion: Routine HF serves as an essential modality in diagnosis and monitoring of SCD. Voxelotor treatment alters the HF profile and may cause difficulty for interpretation. With the emergence of novel therapies, it is imperative for clinicians to provide medication information to clinical laboratories and pathologists to be fully aware of the effects of current treatments to correctly interpret and monitor SCD.